Examining the Mediating Role of Personality on the Relationship between Talent, Technology Systems, and Employee Competency - Dian Fitri; Sri Langgeng Ratnasari; Suyanto; Zulkifli Sultan (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2024)
Human resource management in Indonesian industries plays a critical role in enhancing employee com-petencies amid technological, economic, and global labor market developments. However, there is a gap between employee competencies and organizational demands, reflected in Indonesia's 87th ranking in the Human Capital Index (HCI). This study aims to analyze the influence of talent and technology systems on employee competency, with personality as a mediating variable. Using a quantitative approach with Structural Equation Modeling - Partial Least Squares (SEM-PLS), data were collected from 196 respond-ents out of a population of 385 employees at Putra Kelana Makmur Group. The results indicate that talent does not directly influence employee competency but has an indirect effect through personality. In contrast, technology systems and personality significantly impact competency enhancement. Personality is a significant mediator in the relationships between both talent and technology systems with com-petency. These findings highlight the importance of developing effective technology systems and a supportive work environment that fosters personality development. For companies, this study empha-sizes the need to consider personality and technology as key factors in creating a more holistic and adapt-ive human resource management strategy to improve employee competencies.